Usefulness of guideline recommendations for prognosis in patients with candidemia. (10th November 2018) - Cuervo, Guillermo; Garcia-Vidal, Carolina; Puig-Asensio, Mireia; Merino, Paloma; Vena, Antonio; Martín-Peña, Almudena; Montejo, José Miguel; Ruiz, Alba; Lázaro-Perona, Fernando; Fortún, Jesús; Fernández-Ruiz, Mario; Suarez, Ana Isabel; et al.
Abstract: We aimed to analyze whether the lack of inclusion of specific recommendations for the management of candidemia is an independent risk factor for early and overall mortality. Multicenter study of adult patients with candidemia in 13 hospitals. We assessed the proportion of patients on whom nine specific ESCMID and IDSA guidelines recommendations had been applied, and analyzed its impact on mortality. 455 episodes of candidemia were documented. Patients who died within the first 48 hours were excluded. Sixty-two percent of patients received an appropriate antifungal treatment. Either echinocandin or amphotericin B therapy were administered in 43% of patients presenting septic shock and in 71% of those with neutropenia. Sixty-one percent of patients with breakthrough candidemia underwent a change in antifungal drug class. Venous catheters were removed in 79% of cases. Follow-up blood cultures were performed in 72% of cases. Ophthalmoscopy and echocardiogram were performed in 48% and 50% of patients, respectively. Length of treatment was appropriate in 78% of cases. Early (2–7 days) and overall (2–30 days) mortality were 8% and 27.7%, respectively. Inclusion of less than 50% of the specific recommendations was independently associated with a higher early (HR = 7.02, 95% CI: 2.97–16.57; P < .001) and overall mortality (HR = 3.55, 95% CI: 2.24–5.64; P < .001). In conclusion, ESCMID and IDSA guideline recommendations were not performed on a significant number of patients. Lack of inclusion of these recommendations proved to be an independent risk factor for early and overall mortality.